Sudden Unexpected Death in Neonates: A Clinico-pathological Study. (November 2018) - Reyes, Jeanette A; Somers, Gino R; Chiasson, David A
Clinico-pathological studies that focus on sudden unexpected death (SUD) in the neonatal period are rare. The objective of this study was to elucidate the frequency and pathological spectrum of anatomical causes of death (CODs), found in the setting of sudden unexpected death in neonates (SUD-N), and to correlate the COD with premortem circumstantial information. We conducted a detailed review of all autopsy reports on SUD-N cases at our institution from 1997 to 2015. Analyzed clinical data included obstetrical history, postpartum/neonatal medical course, and circumstances surrounding death. Evaluated autopsy data included growth parameters, pathological findings, ancillary test results, and COD. Data from decedents in which a COD was established (COD-E) were statistically compared with that from decedents in which the COD was undetermined (COD-U). Of 104 neonates (M: 49; F: 55) who fulfilled our inclusion criteria, a COD was established at autopsy in 46 cases (44%). Infections, congenital abnormalities, and inborn errors of metabolism were the most common CODs. Single variables statistically more likely to be found in COD-E neonates were clinical history of prodromal illness, witnessed loss of vital signs, and evidence of physiological stress in the thymus or the liver. A prodrome was statistically more common in the COD-E group, but the absence of a prodrome does not reliably exclude COD-E cases, since over 50% of these patients were asymptomatic prior to their demise. In COD-U neonates, the statistically significant factors were death during sleep, death during sleep while "bed"-sharing, "heavy" lungs, and petechial hemorrhages on the epicardium or pleura. Given the frequency and wide spectrum of underlying pathologies in COD-E neonates, referral of SUD-N cases to pathologists with specialized pediatric autopsy expertise is recommended.